Investigating the Relationship Between Neuronal Cell Death and Early DNA Methylation After Ischemic Injury - Asada, Mayumi; Hayashi, Hideki; Murakami, Kenjiro; Kikuiri, Kento; Kaneko, Ryotaro; Yuan, Bo; Takagi, Norio (Frontiers in Neuroscience, 2020)
Cerebral ischemia induces neuronal cell death and causes various kinds of brain dysfunction. Therefore, prevention of neuronal cell death is most essential for protection of the brain. On the other hand, it has been reported that epigenetics including DNA methylation plays a pivotal role in pathogenesis of some diseases such as cancer. Accumulating evidences indicate that aberrant DNA methylation is related to cell death. However, DNA methylation after cerebral ischemia has not been fully understood yet. The aim of this present study was to investigate the relationships between DNA methylation and neuronal cell death after cerebral ischemia. We examined DNA methylation under the ischemic condition by using transient middle cerebral artery occlusion and reperfusion (MCAO/R) model rats and N-methyl-D-aspartate (NMDA)-treated cortical neurons in primary culture. In this study, we demonstrated that DNA methylation increased in these neurons 1 day after MCAO/R and that DNA methylation, possibly through activation of DNA methyltransferases (DNMT) 3a, increased in such neurons immediately after NMDA treatment. Furthermore, NMDA-treated neurons were protected by treatment with a DNMT inhibitor. Our results showed that DNA methylation would be an initiation factor of neuronal cell death and that inhibition of such methylation could become an effective therapeutic strategy for stroke.